ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN DARING PADA MASA PANDEMI COVID 19 DI SEKOLAH DASAR - Anisya Putri Suryani; Nur Aini Puspitasari (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2022)
With the emergence of the COVID-19 outbreak, face-to-face teaching and learning activities had to be temporarily suspended and replaced with online learning activities. Of course this is the first thing for students in carrying out online learning, and students must interact with new things where online learning uses internet-based learning applications. Which requires students to understand in this online learning. Because of this, many students find it difficult to do online learning. The purpose of this study was to describe students' difficulties in online learning during the COVID-19 pandemic in elementary schools. This type of research uses descriptive qualitative research with oral test, interview, and observation methods. The source of data analysis used in this research is primary data which is carried out directly with students, homeroom teachers, and parents of students, then followed by secondary data. In this study, researchers involved parents of students to understand what difficulties students experienced in online learning.